2022
DOI: 10.1038/s41598-022-14492-4
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing analyses revealed that Salmonella enterica serovar Dublin strains from Brazil belonged to two predominant clades

Abstract: Salmonella Dublin is a cattle-associated serovar sporadically causing disease in humans. S. Dublin strains isolated in Brazil and in other countries were analyzed to determine their phylogenetic relationships, the presence of genes, plasmids, genomic regions related to virulence and antimicrobial resistance genes repertoire, using WGS analyses. Illumina was used to sequence the genome of 112 S. Dublin strains isolated in Brazil from humans (n = 82) and animals (n = 30) between 1983 and 2016. Furthermore, 87 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…isolated from domestic chicken sold in Chungcheong Province showed specific sequence types as the ST of Salmonella spp., which several studies reported were isolated from Brazilian poultry. Salmonella Typhimurium isolated from poultry revealed ST-19 [ 41 , 42 ] and most of the Salmonella Dublin isolates ( n = 112) from human and animal presented ST-10 ( n = 68), ST-3734 ( n = 28), and ST-4030 ( n = 9) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…isolated from domestic chicken sold in Chungcheong Province showed specific sequence types as the ST of Salmonella spp., which several studies reported were isolated from Brazilian poultry. Salmonella Typhimurium isolated from poultry revealed ST-19 [ 41 , 42 ] and most of the Salmonella Dublin isolates ( n = 112) from human and animal presented ST-10 ( n = 68), ST-3734 ( n = 28), and ST-4030 ( n = 9) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The detection of ST-10 in human-derived strains from Denmark ( 7 ) indicates that strains from this ST are able to cause human infections. This assumption is further supported by the detection of ST-10 in human patients from Brazil, Canada, UK, and USA ( 20 ).…”
Section: Discussionmentioning
confidence: 71%
“…MdsA and mdsB can promote resistance to various antibacterial drugs, including phenicol antibiotic, cephalomycin, monobactam, carbapenem, and cephalosporin. This indicates that its presence can lead to resistance to multiple antibiotics [37][38][39][40]. Furthermore, partial regulatory systems contribute to bacterial resistance to heavy metals.…”
Section: Discussionmentioning
confidence: 99%